2015
DOI: 10.7763/ijcea.2015.v6.518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microwave - Induced Torrefaction on Waste Straw Upgrading

Abstract: Abstract-This study focused on upgrading waste straw by developing the technology of microwave-imduced torrefaction and investigating the key operating parameters to improve the energy density and hydrophobicity of biomass for better feedstock for the production of renewable energy. The experiments were conducted under inert environment and atmospheric pressure in a fixed-bed batch reactor putting in a self-designed microwave facility. Factors including microwave power (250 to 450 W), reaction time (10 to 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…Energy yields obtained in this work and the previous ones were in the same range [23][24][25]. To decide the most suitable torrefied condition and configuration regarding to energy yield, the data obtained in the present work and the data reported by the previous works on the fluidized bed reactor [7,19,26], rotating drum reactor [19], convective reactor [19] and microwave reactor [27], were replotted in the HHV ratio-mass yield diagram, as shown in Figure 11. The HHV ratio was defined as the ratio of HHV of torrefied char to HHV of raw biomass.…”
Section: Temperature Distribution Of Cassava Rhizome and Heating Ratementioning
confidence: 65%
“…Energy yields obtained in this work and the previous ones were in the same range [23][24][25]. To decide the most suitable torrefied condition and configuration regarding to energy yield, the data obtained in the present work and the data reported by the previous works on the fluidized bed reactor [7,19,26], rotating drum reactor [19], convective reactor [19] and microwave reactor [27], were replotted in the HHV ratio-mass yield diagram, as shown in Figure 11. The HHV ratio was defined as the ratio of HHV of torrefied char to HHV of raw biomass.…”
Section: Temperature Distribution Of Cassava Rhizome and Heating Ratementioning
confidence: 65%
“…It can be inferred from Figure 10 that the HHV rises with a longer torrefaction time. However, the biomass torrefaction residence time has been shown to be less significant than the temperature in all experiments conducted thus far [20]. The shortest torrefaction residence time can differ depending on the torrefaction temperature, biomass type, the physical and chemical properties of the biomass, and its intended use for a specific sector [46].…”
Section: Effect Of the Torrefaction Residence Timementioning
confidence: 94%
“…Nevertheless, there was a meaningful mass loss at the beginning of the biomass torrefaction process while the change of mass yield was not so important with a longer torrefaction residence time. This can be explained by the decomposition of more reactive components at the beginning of the torrefaction [20]. It was also concluded that the mass yield reduces with the torrefaction residence time.…”
Section: Effect Of the Torrefaction Residence Timementioning
confidence: 95%
See 1 more Smart Citation
“…The majority of the studies listed in Table 1 investigated the effects of different experimental conditions including microwave power, processing time, biomass water content as well as particle size on the characteristics of torrified biomass. The key findings from most of these studies revealed that microwave power and reaction time were the primary factors which affected the torrefaction process, whereas the moisture content of the biomass did not have a significant effect [73][74][75][76]. Due to the fact that water is a good susceptor of MW heating [77], biomass can be directly torrified without the requirement of a pre-drying step.…”
Section: Mw-induced Dry-torrefaction Of Biomassmentioning
confidence: 99%